Interfacial spintronic THz emission - Agarwal, Piyush (2024)
The broken inversion symmetry at the ferromagnet (FM)/heavy-metal (HM) interface leads to spin-dependent degeneracy of the energy band, forming spin-polarized surface states. As a result, the interface serves as an effective medium for converting spin accumulation into 2D charge current through the inverse Rashba–Edelstein effect. Exploring and assessing this spin-to-charge conversion (SCC) phenomenon at the FM/HM interface can offer a promising avenue to surpass the presumed limits of SCC in bulk HM layers. Spintronic heterostructures are utilized as a platform to measure the SCC experienced by photoexcited spin currents. Therefore, FM/HM heterostructures emitting terahertz electric field upon illumination by femtosecond laser pulses enable quantitative measure of the ultrafast SCC process. This results demonstrate a robust interfacial spin-to-charge conversion (iSCC) within a synthetic antiferromagnetic heterostructure, specifically for the NiFe/Ru/NiFe configuration, by isolating the SCC contribution originating from the interface and the bulk heavy-metal (HM). Through the measurements of the emitted terahertz pulse, the iSCC at the NiFe/Ru interface is identified to be ≈27% of the strength as compared to SCC from the highest spin-Hall conducting heavy-metal, Pt. The results thus highlight the significance of interfacial engineering as a promising pathway for achieving efficient ultrafast spintronic devices.